Faktor - Faktor Yang Memengaruhi Internet Financial Reporting (IFR) Pada Perusahaan Manufaktur - Muhammad Akram Pramudhani, Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims at how the role of profitability, firm size, public ownership on internet financial reporting on manufacturing industry listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 77 companies. Data processing techniques using multiple regression analysis what helped by SPSS program (Statistical Product and Service Solution) 25 for Windows and Microsoft Excel 2016. The results of this study indicate that public ownership have a significant influence on internet financial reporting, and the rest variables doesn’t have influence on internet financial reporting. The implication of this study is in the practice, financial reporting is carried out by manufacturing companies as a form of their responsibility to the public.